The Participatory Budget Experiment in Delhi and Warsaw: A Comparison - Iwanek, Krzysztof (International Journal For Research In Business, Management And Accounting, 2016)
The aim of this paper is to compare the two fresh and in-progress experiments in participatory budget on local level in two state capitals: New Delhi in India and Warsaw in Poland. As of now, the recently chosen AAP government has introduced participatory budget as an experiment in 2015 in 11 legislative assembly constituencies of Delhi. In Poland, however, such exercises have been introduced in a number of cities in all of their administrative areas and therefore the exercise straddles the Polish political divides. Therefore, I would like analyse how can the Warsaw participatory budget experience be relevant and inspiring for the ongoing Delhi participatory budget exercise. This paper was originally presented and the ‘Economics and Politics of Local Governments: The Indian Experience’ conference, Institute of Development Studies, Kolkata, December 28-29, 2015.